Audiogenic epileptic DBA/2 mice strain as a model of genetic reflex seizures and SUDEP - Bosco, Francesca; Guarnieri, Lorenza; Leo, Antonio; Tallarico, Martina; Gallelli, Luca; Rania, Vincenzo; Citraro, Rita; De Sarro, Giovambattista (Frontiers in Neurology, 2023)
Epilepsy is a chronic neurological disease characterized by abnormal brain activity, which results in repeated spontaneous seizures. Sudden unexpected death in epilepsy (SUDEP) is the leading cause of seizure-related premature death, particularly in drug-resistant epilepsy patients. The etiology of SUDEP is a structural injury to the brain that is not fully understood, but it is frequently associated with poorly controlled and repeated generalized tonic–clonic seizures (GTCSs) that cause cardiorespiratory and autonomic dysfunctions, indicating the involvement of the brainstem. Both respiratory and cardiac abnormalities have been observed in SUDEP, but not much progress has been made in their prevention. Owing to the complexity of SUDEP, experimental animal models have been used to investigate cardiac and/or respiratory dysregulation due to or associated with epileptic seizures that may contribute to death in humans. Numerous rodent models, especially mouse models, have been developed to better understand epilepsy and SUDEP physiopathology. This review synthesizes the current knowledge about dilute brown agouti coat color (DBA/2) mice as a possible SUDEP model because respiratory arrest (RA) and sudden death induced by audiogenic generalized seizures (AGSs) have been observed in these animals. Respiratory/cardiac dysfunction, brainstem arousal system dysfunction, and alteration of the neurotransmitter systems, which are observed in human SUDEP, have also been observed in these mice. In particular, serotonin (5-HT) alteration and adenosine neurotransmission appear to contribute to not only the pathophysiological mechanisms of medication but also seizure-related respiratory dysfunctions in this animal model. These neurotransmitter systems could be the relevant targets for medication development for chronic epilepsy and SUDEP prevention. We reviewed data on AGSs in DBA/2 mice and the relevance of this model of generalized tonic–clonic epilepsy to human SUDEP. Furthermore, the advantages of using this strain prone to AGSs for the identification of possible new therapeutic targets and treatment options have also been assessed.